Ranges in silicon of ions with atomic numbers 62 ⩽ Z1 ⩽ 66 at 100 keV. - Baragiola, R. A.; Chivers, D.; Dodds, D.; Grant, W. A.; Williams, J. S. (1976)
Fil: Baragiola, R. A. Comisión Nacional de Energía Atómica; Argentina